Gender in Audit Committee and Financial Reporting Timeliness: the Case of Unique Continental European Model - ., Zaitul; Ilona, Desi (International Journal of Engineering and Technology, 2018)
The goal of the current research is to identify whether or not the gender of Audit Committee members affects the timeliness of financial reporting. Unlike several studies which have focused on gender in the Board of Directors, the current study more specifically discusses gender in the Audit Committee in a country which adopts a Continental European System. This study employs panel data analysis for 370 observations of 185 Indonesian listed companies in the 2014-2015 period. This research reports that gender of the Audit Committee members is still debatable with regards to their role in improving the timeliness of financial reporting. Further, size, independence, expertise, and Audit Committee activities have an insignificant impact on the timeliness of financial reporting.Â Â